Temporal GPR imaging of an ethanol release within a laboratory-scaled sand tank - Glaser, D.R.; Werkema, D.D.; Versteeg, R.J.; Henderson, R.D.; Rucker, D.F. (Journal of applied geophysics, 2012)
Within the last decade efforts in geophysical detection and monitoring of fossil fuel releases into the subsurface have shown increasing success, including the ability to geophysically detect and delineate enhanced and natural biodegradation and remediation activities. The substitution of biofuels, such as ethanol, for fossil fuels is becoming persistent in the national and international marketplaces making it subject to the same types of accidental releases and exposure scenarios currently associated with the transport and storage of fossil fuels. Thus, there is interest from both academics and regulators to investigate the feasibility of applying geophysical methodologies to biofuel releases. In this study, we performed experimental and numerical investigations on the feasibility of using ground penetrating radar (GPR) to monitor the migration of an ethanol release. A tank scale model of a closed hydrologic system was prepared with Ottawa sand and instrumented with an automated gantry measurement apparatus for time-lapse measurement of zero offset and coincident GPR reflections on multiple horizontal planes. Measurements were acquired in the unsaturated and saturated zones throughout the injection and transport of the ethanol release. The results of the monitoring suggest a measureable contrast within both time and frequency domains of the GPR data coincident with the ethanol release and subsequent migration. We conclude that the monitoring of ethanol in a sand matrix at various levels of saturation is possible with GPR. ► Detection of ethanol in Ottawa sand at three saturation states using GPR. ► Simulated pipeline release of ethanol imaged using ground penetrating radar. ► Lab scale 4D automated gantry data acquisition of GPR for a subsurface EtOH release. ► Amplitude attenuation and velocity analysis of GPR for ethanol detection. ► GPR power spectrum analysis performed for detection of ethanol.